Detection rate of serrated polyps and serrated polyposis syndrome in colorectal cancer screening cohorts: a European overview. Issue 7 (24th February 2016) - IJspeert, J E G; Bevan, R; Senore, C; Kaminski, M F; Kuipers, E J; Mroz, A; Bessa, X; Cassoni, P; Hassan, C; Repici, A; Balaguer, F; Rees, C J; et al.
Abstract : Objective: The role of serrated polyps (SPs) as colorectal cancer precursor is increasingly recognised. However, the true prevalence SPs is largely unknown. We aimed to evaluate the detection rate of SPs subtypes as well as serrated polyposis syndrome (SPS) among European screening cohorts. Methods: Prospectively collected screening cohorts of ≥1000 individuals were eligible for inclusion. Colonoscopies performed before 2009 and/or in individuals aged below 50 were excluded. Rate of SPs was assessed, categorised for histology, location and size. Age–sex–standardised number needed to screen (NNS) to detect SPs were calculated. Rate of SPS was assessed in cohorts with known colonoscopy follow-up data. Clinically relevant SPs (regarded as a separate entity) were defined as SPs ≥10 mm and/or SPs >5 mm in the proximal colon. Results: Three faecal occult blood test (FOBT) screening cohorts and two primary colonoscopy screening cohorts (range 1.426–205.949 individuals) were included. Rate of SPs ranged between 15.1% and 27.2% (median 19.5%), of sessile serrated polyps between 2.2% and 4.8% (median 3.3%) and of clinically relevant SPs between 2.1% and 7.8% (median 4.6%). Rate of SPs was similar in FOBT-based cohorts as in colonoscopy screening cohorts. No apparent association between the rate of SP and gender or age was shown. Rate of SPS ranged from 0% to 0.5%, which increased to 0.4% to 0.8% after follow-up colonoscopy. Conclusions: The detection rate of SPs is variable among screening cohorts, and standards for reporting, detection and histopathological assessment should be established. The median rate, as found in this study, may contribute to define uniform minimum standards for males and females between 50 and 75 years of age.